Answering the Challenge of Industrial Revolution 4.0 Through Improved Skills Use of Technology College - Tanjung, Romi Fajar (Universitas Malikussaleh, 2019)
The era of the industrial revolution 4.0 requires working effectively and efficiently, all the activities is quick and easy. Skills use of technology is one of learning skills that must be mastered to achieve success in life in the era of industrial revolution 4.0, especially in the academic field for students undertaking study or the study completion. Skills good use of technology will make the students quickly and easily complete the study. This study aims to analyze the importance of skills enhancement technology use in higher education in order to meet the industrial revolution 4.0. The research sample student counseling. Research data analysis using percentage. The research found that the importance of improving the skills of the use of technology in higher education and in general skills of student technology use is not optimal.